PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA PEMBELAJARAN FISIKA KELAS X SMKN 2 PINRAN - Sukriadi; Sixtus Iwan Umboh; Jimmy Lolowang (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
This research is quasi-experimental research aimed at determining whether Jigsaw's collaborative learning has a positive effect on the learning outcomes of Grade X SMK Negeri 2 PINRANG (on straight motion material) students. The research design was